Putting the State In Its Place: US Foreign Policy and Differential Accumulation in Middle-East “Energy Conflicts” - Shimshon Bichler; Jonathan Nitzan (Review of International Political Economy, 1996)
This is the second in a series of two articles looking into the interaction between differential capital accumulation and Middle East “energy conflicts.” Examining the historical record since the late 1960s, we find US policies to have been increasingly consistent with the coinciding differential interests of a Weapondollar-Petrodollar coalition of large defence contractors and oil companies. Contrary to aggregate views which emphasize the “national interest” or the broad imperatives of capital accumulation – but in line with the differential interests of these companies – US policies in the region seem to have contributed toward greater instability, imposed limits on the free flow of oil and led to higher unstable prices. Most significantly, every “energy conflict” since the late 1960s was preceded by adverse drops in the differential rate of the large oil companies, which then promptly removed in the wake of the ensuing crisis. While the US government was officially seeking regional conciliation, it passively or actively endorsed each one of these conflicts. The current peace drive between Israel and its Arab neighbours is overshadowed by negative differential profits for the oil companies and depressed weapon sales for the arms contractors. Left unresolved, these predicaments could eventually culminate in a new “energy conflict.”
Keywords: 330; arms; accumulation; capital; capitalism; conflict; corporation; crisis; distribution; elite; energy; finance; globalization; growth; imperialism; GPE; liberalism; Middle East; military; national interest; neoliberalism; new world order; oil; OPEC; ownersh